![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
解方程:(x+5)(x-7)=x(x+2)+1
3个回答
展开全部
x=-9
过程:
(x+5)(x-7)=x(x+2)+1
x^2 +(-7+5)* x -35=x^2 + 2x +1
-36=4x
x=-9
过程:
(x+5)(x-7)=x(x+2)+1
x^2 +(-7+5)* x -35=x^2 + 2x +1
-36=4x
x=-9
展开全部
解:原式=x²-7x﹢5x-35=x²﹢2x﹢1
x²-7x﹢5x-x²-2x=1+35
﹣4x=36
x=﹣9
x²-7x﹢5x-x²-2x=1+35
﹣4x=36
x=﹣9
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
解:x²-7x+5x-35=x²+2x+1
x²-2x-35=x²+2x+1
x²-x²-2x-2x=35+1
-4x=36
x=-9
x²-2x-35=x²+2x+1
x²-x²-2x-2x=35+1
-4x=36
x=-9
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询